THE SOCIAL LEGITIMACY OF GOLF TOURISM: AN APPLICATION TO THE GOLF COURSES OF ANDALUSIA - Riquel-Ligero, Francisco (ENLIGHTENING TOURISM. A PATHMAKING JOURNAL)
<!–[if gte mso 9]> Normal 0 21 false false false ES X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <![endif]–> <!–[if gte mso 9]> Normal 0 21 false false false ES X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <![endif]–> Today, respect for the natural environmental is a variable that plays an important role when it comes to configuring a tourist destination or product, particularly since this is an industry for which the location is irrevocably fixed. Andalusia, in particular, has become well-established as a major golf tourism destination. It has more golf courses than any other of the 17 Spanish Autonomous Regions. This has stimulated a debate on the environmental impacts of sporting facilities of this type, with attention consequently focused on the need of these tourism companies to achieve and maintain social legitimacy. In the work described here, the Partial Least Squares (PLS) technique is applied to analyse the impact of the institutional context on the implementation of environmental practices and the achievement of social legitimacy by these organisations.